2021
DOI: 10.21203/rs.3.rs-381243/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is the recorded economic cost of alien invasive fishes worldwide?

Abstract: Invasive alien fishes have caused pernicious ecological impacts on aquatic ecosystems. However, there has not been a global appraisal of associated economic impacts. Here, we compiled reported economic impacts of invasive alien fishes using the most comprehensive global database of invasion costs (InvaCost). We analyze how fish invasion costs are distributed geographically and temporally, as well as which socioeconomic sectors are most impacted. Fish invasions have caused the economic loss of at least US$32.8 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The lack of reported costs found for the vast majority of reported alien species corroborates other studies at various spatial and taxonomic scales, including for the United Kingdom 37 , Singapore and Southeast Asia 35 , fishes 49 , and ants 50 , among others. Concerning sectors of economic activity for amphibians, most costs impacted authorities-stakeholders.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of reported costs found for the vast majority of reported alien species corroborates other studies at various spatial and taxonomic scales, including for the United Kingdom 37 , Singapore and Southeast Asia 35 , fishes 49 , and ants 50 , among others. Concerning sectors of economic activity for amphibians, most costs impacted authorities-stakeholders.…”
Section: Discussionsupporting
confidence: 86%
“…For example, non-native fish species listed in the German Blacklist (Essl et al 2011) were missing entirely, indicating a profound lack of cost information. Alien fish species, in particular, are known to be very costly in other regions, such as North America (Haubrock et al 2021b). Other regional studies of the InvaCost database have similarly found that the number of species with recorded costs represent a very small percentage of known alien species.…”
Section: Discussionmentioning
confidence: 99%
“…2). Taxonomic studies can be 'nested' at different scales, such as analyses of aquatic invaders as a whole followed by a detailed assessment for invasive fish (Haubrock et al 2022), or a compilation of costs of terrestrial invertebrates (Renault et al 2022a) followed by a specific assessment of ants . Such distinctions are useful because, while a higher level of classification can reveal the general state of knowledge, different management strategies are often needed for specific taxonomic groups, and organisations/stakeholders can have particular taxonomic foci.…”
Section: Capturing the Multi-faceted Nature Of Invasion Costsmentioning
confidence: 99%